We Don't Even Have a Name For It. (19th July 2016) - Slaney, Clare
Abstract: Despite being rooted in radical departures from institutionalized ways of caring for the mentally unwell, the psy‐professions find themselves repeating patterns of the past when it comes to the psychological treatment of people who are very poor. In the UK professional counselling and psychotherapy bodies have embraced neo‐liberal philosophies of individualism: locating responsibility for personal failure in the individual, positivity, and of employment being an absolute good. The psy‐professions, at both executive and membership level, seem unaware that the philosophical foundations of government‐funded initiatives purporting to help people with mental heath problems are based in political ideology rather than psychological research. In a profession where employment itself is rare, "opportunities for counsellors" has been the primary focus for the professions whilst the voices of people negatively affected by this ideology remain unheard. But things may be about to change. Focusing on the British Association for Counselling and Psychotherapy, the largest professional body representing counsellors and psychotherapists, this paper offers a view of how the psy‐professions have unthinkingly implemented harmful and unethical political ideology; highlights some of the inconsistencies and cognitive dissonance involved in the implementation of those policies; and offers some hope for change. Copyright © 2016 John Wiley & Sons, Ltd.